Giuseppe Mazzini and the Origins of Fascism - Levis Sullam, Simon. author. aut Link
X, 206 p.
Keywords: This controversial and groundbreaking study proposes a compelling reinterpretation of the political thought of one Italy's founding fathers, Giuseppe Mazzini (1805-1872), and in the process suggests a new approach to understanding the origins of fascist ideology.